A comparative study on the effect of household water treatment on diarrhoea morbidity among under-fives in Plateau State, Nigeria using two treatment modalities - Okoh, Elizabeth Onyi; Envuladu, Esther Awazzi; Miner, Chundung Asabe; Mohammed, Amina; Ode, Gloria Nengi; Zoakah, Ayuba Ibrahim (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Consumption of unsafe water contributes to diarrhoeal burden in sub-Sahara Africa. This burden can be reduced by simple and affordable methods of household water treatment. The study aims at comparing the effect of two of such methods on diarrheal burden among under-fives in rural communities of Plateau State.Methodology: A community-based quasi experimental study was conducted among 202 underfive-caregiver pairs in two selected rural communities of Plateau State, involving household water treatment with flocculant-disinfectant powder in intervention group and sodium hypochlorite solution in control group respectively. History of diarrhoea before intervention, at 2 weekly intervals during the intervention and after intervention was assessed. Data obtained was analyzed using SPSS version 23. Prevalence and incidence of diarrhoea were calculated and compared among the two groups.Result: Diarrhoea prevalence at pre-intervention was 19.6% in flocculant-disinfectant group and 17.0% in sodium hypochlorite group. At post intervention, the prevalence reduced significantly by 94.7% (19.6% to 1%) in intervention group and by 76.5% (17% to 4.2%) in control group. There was no statistical significant difference in the prevalence of diarrhoea between the two groups, however, diarrhoea incidence in the sodium hypochlorite group (1.12 episode per child per year) was significantly higher than the incidence in the flocculant-disinfectant group (0.59 episodes per child per year) with a  risk-ratio of 1.93 (95% CI: 1.037 - 3.703).Conclusion: Household water treatment with flocculant-disinfectant reduced diarrhoea burden better than sodium hypochlorite. This technology should be made more available and assessible to rural communities where diarrhea burden is high.